Mites (Acari: Mesostigmata, Sarcoptiformes and Trombidiformes) associated to soybean in Brazil, including new records from the Cerrado areas. - REZENDE, J. M. (2012)
In Brazil, soybean Glycine max (L.) Merril crops are subjected to incidence of several pests, which are mainly insect species. However, the occurrences of other pest species are growing. In this context, outbreaks of phytophagous mites are becoming more frequent. Nevertheless, records of mites in such crop are available only for Maranhão, Mato Grosso, Minas Gerais and Rio Grande do Sul states. Thus, this work gathers all information published about the diversity of mites found in soybean in Brazil, and also new records of mite species made on samplings taken from the central Cerrado area. In the whole, occurrence of 44 species of plant mites in soybean has been recorded in Brazil. Data from prior studies and the results of this work present the tetranychid Mononychellus planki (McGregor) as the mite species most frequently occurring in the Brazilian soybean crops. A large portion of Phytoseiidae species has occurred in crops from Rio Grande do Sul state. In addition, spontaneous soybean has hosted almost half of the phytoseiid species sampled in Cerrado region. High diversity of Tarsonemidae has been found in the cultivated soybean. More studies about soybean mites are needed to clarify the damage potential of phytophagous mites and the biological role of predatory mites in this crop. RESUMO: No Brasil, lavouras de soja Glycine max (L.) Merril estão sujeitas a incidência de várias pragas, as quais são principalmente espécies de insetos. No entanto, a ocorrência de outras espécies-praga tem aumentado. Neste contexto, surtos populacionais de ácaros fitófagos têm se tornado mais frequentes. Apesar disso, os registros de ácaros para esta cultura estão disponíveis apenas para os estados de Maranhão, Mato Grosso, Minas Gerais e Rio Grande do Sul. Assim, este trabalho agrega toda a informação publicada sobre a diversidade de ácaros encontrados em soja no Brasil, além de novos registros feitos através de amostragens na região central do Cerrado. No total, 44 espécies de ácaros foram registradas em soja no Brasil. Dados de estudos anteriores, somados aos resultados deste trabalho, apresentam o tetraniquídeo Mononychellus planki (McGregor) como a espécie de ácaro mais frequente em lavouras de soja brasileiras. Considerável número de espécies de Phytoseiidae tem ocorrido nas lavouras amostradas do Rio Grande do Sul. Além disso, a soja espontânea abrigou quase metade das espécies de fitoseídeos amostrados na região central do Cerrado. Por sua vez, uma elevada diversidade de Tarsonemidae foi encontrada na soja cultivada. Mais estudos sobre ácaros em soja são necessários para esclarecer o potencial de dano dos ácaros fitófagos e o papel biológico dos ácaros predadores nesta cultura.